Ethnobotanical uses, phytochemistry and biological activity of the genus Euclea: A review - Taye, Abebe Dagne; Bizuneh, Gizachew Kassahun; Kasahun, Asmamaw Emagn (Frontiers in Pharmacology, 2023)
Euclea (Ebenaceae) is a genus of flowering shrubs and trees widely distributed in Africa, the Comoro Islands, and Arabia. This review aimed to evaluate the ethnobotanical uses, phytochemistry, and biological activities of the genus Euclea on available research reports. This was achieved through PubMed, Medline, Google Scholar, Science Direct, Taylor and Francis Online, Wiley Online Library which provides access to scientific and medical research. The extensive literature survey revealed that plants that belong to this genus are used as folkloric medicine for the treatment of diabetes mellitus, toothache, diarrhea, cancer, malaria, leprosy, and genital and oral diseases in the case of HIV/AIDS-related diseases. To date, more than 40 secondary metabolites have been isolated and identified from these plants, especially from E natalensis and E. divinorum. Among these, naphthoquinones, terpenes, and flavonoids are potential secondary metabolites with profound biological activities. Euclea plant extracts and their bioactive compounds possess outstanding pharmacological properties, especially antimalarial, antidiabetic, anticancer, antimicrobial, and antioxidant properties.